Integrated assessment of brackish water induced deleterious impacts: Analysis of hemato-biochemistry, erythrocytic toxicity, histopathology and oxidative stress biomarkers of mrigal carp - Ghulam Ali Raza; Riaz Hussain; Abdul Ghaffar; Mudassar Mohiuddin; Roshan Riaz; Shah Nawaz; Mükremin Ölmez; Dalia Fouad; Promy Virk (PLoS ONE, 2026)
Salinity is recognized as one of the most detrimental abiotic stressors, inducing a range of cellular and biochemical disruptions in both marine and freshwater organisms worldwide. In this study, 84 healthy specimens of mrigal carp ( Cirrhinus mrigala ) were randomly selected and assigned to four experimental groups (T0, T1, T2, and T3). Each group was maintained under standardized laboratory conditions and exposed to different salinity levels (0, 3, 5, and 7 ppt) in brackish water to evaluate the resulting toxico-physiological responses over 90 days interval. Hematological analysis revealed a significant reduction in erythrocyte count, hemoglobin concentration, hematocrit values, and lymphocyte percentage in salinity-exposed (5, and 7 ppt) fish. In contrast, a notable elevation in total white blood cell (WBC) count and neutrophil population was observed in fish exposed to salinity (5, and 7 ppt) at days 60 and 90 of study. Biochemical assessment of serum parameters demonstrated a marked decline in albumin triglycerides and glucose levels, whereas concentrations of lactate dehydrogenase (LDH), cholesterol, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), creatinine, and urea increased significantly in fish at days 60 and 90 of trial subjected to salinity (5, and 7 ppt). A significant elevation in oxidative stress biomarkers was observed in fish exposed to brackish water (5, and 7 ppt), accompanied by a substantial decline in the activity of key antioxidant enzymes, including glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) in erythrocytes. Histopathological examination of visceral organs—such as the gills, kidneys, liver, brain, and heart—revealed pronounced tissue damage and pathological alterations, particularly in fish exposed to higher salinity levels (5and 70 ppt). Overall, the findings indicate that elevated salinity in brackish water can provoke oxidative stress, impair hematological and biochemical homeostasis, suppress antioxidant defense mechanisms in erythrocytes, and induce microscopic ailments in different visceral organs of fresh water fish in a time dependent response. In conclusion, hematological and biochemical biomarkers are useful tools and provide reliable information about immune potential, level of stress, intoxication and severity of histopathological lesions.